On the relation between a green and bright window view and length of hospital stay in affective disorders - Anna Mascherek; Sandra Weber; Kevin Riebandt; Carlos Cassanello; Gregor Leicht; Timothy Brick; Jürgen Gallinat; Simone Kühn (European Psychiatry, 2022)
Abstract